Dialectical Behaviour Therapy and Acceptance and Commitment Therapy for Eating Disorders: Mood Intolerance as a Common Treatment Target - Shumlich, Erin J. (Canadian Journal of Counselling and Psychotherapy, 2017)
Dialectical behaviour therapy (DBT) and acceptance and commitment therapy (ACT) are third-wave cognitive behavioural therapies that are beginning to show promise in the treatment of eating disorders. Mood intolerance—difficulty dealing with intense emotional states—is an important factor influencing the onset and maintenance of eating disorder pathology. Emotional regulation in DBT and experiential acceptance in ACT have similar mechanisms of change, specifically targeting mood intolerance. DBT and ACT have similar cognitive and behavioural roots and share a focus on mindfulness- and acceptance-based techniques. This theoretical review article compares mood intolerance in DBT and ACT in the treatment of eating disorders. Mood intolerance should be considered in future empirical work and incorporated into treatment of eating disorders.